2020
DOI: 10.21082/jpptp.v4n2.2020.p105-111
|View full text |Cite
|
Sign up to set email alerts
|

Optimalisasi Lahan Budidaya Tumpangsari Padi dan Jagung: Pengaruh Kombinasi Varietas terhadap Produktivitas

Abstract: <p>Produksi padi dan jagung dapat ditingkatkan melalui optimalisasi lahan dengan pola tumpangsari. Tidak optimalnya produktivitas padi dan jagung dalam pola tanam tumpangsari mungkin disebabkan oleh kombinasi varietas yang kurang tepat. Tujuan penelitian ini adalah mengidentifikasi kombinasi varietas padi dan varietas jagung yang tepat dalam pola tanam tumpangsari, untuk memperoleh produktivitas yang tinggi. Penelitian dilakukan di Desa Durian, Kecamatan Gentuma Raya, Gorontalo, pada MT 2018/2019, menggu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…These advantages include tolerance to biotic stresses (pests and diseases) and tolerance to environmental stresses (low pH, low soil nutrients, drought, inundation). Compared to other high-yielding varieties, local rice varieties were superior in intercropping with maize [41] and more tolerant of immersion at 20 days after partial IOP Publishing doi:10.1088/1755-1315/1172/1/012005 7 submergence at the vegetative stage [42]. The growth response of local rice seedlings in submerged conditions indicates inundation tolerant plants.…”
Section: Availability and Performance Of Local Varieties Of Soak-resi...mentioning
confidence: 95%
See 1 more Smart Citation
“…These advantages include tolerance to biotic stresses (pests and diseases) and tolerance to environmental stresses (low pH, low soil nutrients, drought, inundation). Compared to other high-yielding varieties, local rice varieties were superior in intercropping with maize [41] and more tolerant of immersion at 20 days after partial IOP Publishing doi:10.1088/1755-1315/1172/1/012005 7 submergence at the vegetative stage [42]. The growth response of local rice seedlings in submerged conditions indicates inundation tolerant plants.…”
Section: Availability and Performance Of Local Varieties Of Soak-resi...mentioning
confidence: 95%
“…In potential tidal areas, the yield of Inpara 3 reached 4.04 t/ha [30]. Various research results reported that the performance of Inpara 3 results in lowland swamp lands, ranged from 3.56-5.58 t/ha (31,32,33,26]. Source: [27]…”
Section: Availability Of New Superior Varieties Of Submergence Resist...mentioning
confidence: 99%
“…For rice plants use Phonska fertilizer 250 kg / ha, Urea 150 kg/ha and KCl 50 kg/ha, while for corn plants are Phonska fertilizer 350 kg / ha and Urea 200 kg / ha dan KCl 100 kg/ha. [5] While for for monoculture rice and corn is according to the existing farmer. The parameters for rice were measured pest and disease attack, plant growth and development, rice production and analysis of soil sample and farming system analysis (social economic), while for corn crops include plant growth development and corn production, weight of 100 maize grains and analysis of farming economically of corn intercropping and monoculture cultivation of corn and rice as farmer's existing.…”
Section: The Implementation Of the Rice-corn Cropping Patternmentioning
confidence: 99%